Technical analysis on the Bitcoin market: Trading opportunities or investors' pitfall? - Marina Resta; Paolo Pagnottoni; Maria Elena De Giuli (Risks, 2020)
In this paper we aimed to examine the profitability of technical trading rules in the Bitcoin market by using trend-following and mean-reverting strategies. We applied our strategies on the Bitcoin price series sampled both at 5-min intervals and on a daily basis, during the period 1 January 2012 to 20 August 2019. Our findings suggest that, overall, trading on daily data is more profitable than going intraday. Furthermore, we concluded that the Buy and Hold strategy outperforms the examined alternatives on an intraday basis, while Simple Moving Averages yield the best performances when dealing with daily data.
Keywords: C22; G10; 330; technical analysis; trading rules; profitability; Bitcoin